GENETIC VARIABILITY AND CORRELATION STUDIES FOR SEED COTTON YIELD AND FIBRE QUALITY PARAMETERS IN DIVERSE COTTON GENOTYPES - CHEERLA PAVAN,; RANI CHAPARA,; M. SUDHA RANI,; G. A. DIANA GRACE,; M. JAMES,; V. PRIYADHARSHINI, (The Journal of Research ANGRAU, 2025)
An experiment was executed at RARS, Lam, Guntur during the kharif, 2024 to determine variability and correlation studies across 50 cotton genotypes, including three check varieties (NDLH 2051-1, Sivanandhi, and CICR 23 Bt) for 14 traits in an Augmented Block Design.  ANOVA revealed significant differences among the 53 cotton genotypes for all the 14 traits, indicating substantial variability within the experimental material,that could be used for further crop  improvement. Genotypic coefficient of variation and phenotypic coefficient of variation were high for number of monopodia per plant,boll weight and seed cotton yield per plant. High heritability coupled with high genetic advance was observed for plant height, number of monopodia per plant, number of bolls per plant, boll weight, lint index, seed index and seed cotton yield per plant rendering the probability of selecting genotypes for these characters which would behave with fidelity being the additive gene action in the inheritance of these attributes. Correlation study demonstrated a significant positive relationship between seed cotton yield per plant and plant height, number of bolls per plant, boll weight, seed index and lint index, indicating direct selection could be preferable for improving the seed cotton yield per plant.The genotypes LHBT 2203, LHBT 9, L 2278 and L 2281 were identified as the best performers for lint index, seed index and seed cotton yield per plant; while Suvin, CCB 29, L 2275, L 2385 and L 2268 for fibre quality traits.